Feasibility of endoscopic ultrasound-guided hepaticogastrostomy using a 22-gauge needle. Issue 44 (4th November 2022) - Takahashi, Koji; Ohyama, Hiroshi; Ouchi, Mayu; Kan, Motoyasu; Nagashima, Hiroki; Iino, Yotaro; Kusakabe, Yuko; Okitsu, Kohichiroh; Ohno, Izumi; Takiguchi, Yuichi; Kato, Naoya
Abstract : This study aimed to evaluate the feasibility of performing endoscopic ultrasound-guided hepaticogastrostomy using a 22-gauge fine-needle aspiration needle. This was a single-center retrospective study. Fourteen patients who underwent endoscopic ultrasound-guided hepaticogastrostomy with a 22-gauge fine-needle aspiration needle were examined. Fourteen eligible patients were included in this study. The age of patients ranged from 55 to 93 years, with a median of 76 years. Of patients with existing underlying diseases, there were 8 cases of pancreatic cancer (57.1%), 2 cases of metastatic liver tumor (14.3%), 2 cases of bile duct stones (14.3%), 1 case of hilar cholangiocarcinoma (7.1%), and 1 case of gallbladder cancer (7.1%). Regarding gastrointestinal anatomy, there were 11 cases (78.6%) of normal and 3 cases (21.4%) of gastric resection with Roux-en-Y. Reasons for endoscopic ultrasound-guided hepaticogastrostomy were duodenal obstruction in 7 cases (50.0%), surgically altered anatomy in 3 cases (21.4%), and 4 cases (28.6%) of failed endoscopic retrograde cholangiopancreatography. Technical success was achieved in 11 cases (78.6%). Subsequently, 11 cases of technical success were analyzed. There were 5 cases of puncturing B2 (45.5%). The puncture bile duct diameter ranged from 3.1 to 5.7 mm, with a median of 4.4 mm. endoscopic ultrasound-guided antegrade procedures was combined with endoscopic ultrasound-guided hepaticogastrostomy in 2 cases (18.2%). Clinical success was achieved in all the cases. The procedure time ranged from 15 to 93 minutes, with a median duration of 35 minutes. Regarding the type of stent placed in hepaticogastrostomy, a plastic stent was placed in 10 cases (90.9%) and a metal stent was placed in 1 case (9.1%). Early adverse events occurred in 4 cases (36.4%), and all of these cases developed biliary peritonitis, late adverse events occurred in 1 case (9.1%), this was biloma. A change to a 0.025-inch guidewire during the procedure was required in 8 cases (72.7%). Esophageal puncture was not performed. endoscopic ultrasound-guided hepaticogastrostomy using a 22-gauge fine-needle aspiration needle is effective. However, in 72.7% of the cases started using the 0.018-inch guidewire, the guidewire was exchanged for a 0.025-inch guidewire during procedure.